2014
DOI: 10.14257/ijsh.2014.8.4.05
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Key Factors Affecting Information Disclosure Intention in Online Shopping

Abstract: Abstracts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
9
1
Order By: Relevance
“…Second, the results have revealed that social interaction has a positive influence on the depth and breadth of self-disclosure of information via MIM apps, while social influence does not. This finding is inconsistent with the results of previous studies which have found that social influence has a significant impact on information disclosure within different context, such as SNS (Shibchurn and Yan, 2015) and online shopping environment (Wang and Liu, 2014). One possible explanation of our result is that users are motivated to disclose intimate information and discuss various topics in an effort to maintain and extend their relationships with other MIM apps users, while the pressure from other users has no a significant influence on their decision to disclose information.…”
contrasting
confidence: 99%
“…Second, the results have revealed that social interaction has a positive influence on the depth and breadth of self-disclosure of information via MIM apps, while social influence does not. This finding is inconsistent with the results of previous studies which have found that social influence has a significant impact on information disclosure within different context, such as SNS (Shibchurn and Yan, 2015) and online shopping environment (Wang and Liu, 2014). One possible explanation of our result is that users are motivated to disclose intimate information and discuss various topics in an effort to maintain and extend their relationships with other MIM apps users, while the pressure from other users has no a significant influence on their decision to disclose information.…”
contrasting
confidence: 99%
“…Notably, people in an individualist society were more likely to consider benefits when disclosing information—compared to those in inclusive collectivist and high power-distance cultures. Z. Wang and Liu (2014), identified the social influence of friends, family, and colleagues as a significant factor in directing people to disclose personal information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While there exist a number of studies to measure privacy attitudes and behaviors in online interactions, [1], [27], [30], we wanted to get a sense of privacy attitudes in both online and offline behaviors. Therefore we use the Westin's [32,33,34,35,36,37,38] studies to gain a holistic understanding of privacy concerns exhibited by individuals'.…”
Section: Related Workmentioning
confidence: 99%